PERAN AUDIT FORENSIK DALAM UPAYA PENGUNGKAPAN KORUPSI di INDONESIA - Ayu Kristiani Panggabean; David Adechandra Ashedica Pesudo (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to find out how forensic audits at the Financial and Development Supervisory Agency Riau Representative in revealing corruption, this qualitative study used primary and secondary methods which from the primary used interview techniques with four employees of the Riau Representative Development and Financial Supervisory Agency (BPKP), People in Pekanbaru and from the secondary use Law number 20 of 2001 concerning "Eradication of Corruption Crimes". Data on the Corruption Perception Index (GPA) and various articles on the disclosure of corruption. This study reveals that corruption is one type of fraud so that forensic audit detection is carried out faster and easier because the procedures are focused, detailed and rigid. So it can be concluded that the forensic audit in revealing corruption uses the Fraud Control Plan (FCP) as a tool in carrying out its duties.